Does Lack of Knowledge Lead to Misperceptions? Disentangling the Factors Modulating Public Knowledge About and Perceptions Toward Sharks - Afonso, André S.; Roque, Pedro; Fidelis, Leonardo; Veras, Leonardo; Conde, Anxo; Maranhão, Paulo; Leandro, Sérgio; Hazin, Fábio H. V. (Frontiers in Marine Science, 2020)
Identifying sources of variability in public perceptions and attitudes towards sharks can assist managers and conservationists with developing effective strategies to raise awareness and support for the conservation of threatened shark species. This study examined the effect of several demographic, economic and socioenvironmental factors on the quality of knowledge about and perceptions towards sharks in two contrasting scenarios from northeastern Brazil: a shark hazardous coastal region and a marine protected insular area. Ordered logistic regression models were built using Likert data collected with a self-administered questionnaire survey (N = 1094). A clear relationship between education, knowledge and perceptions was evidenced, with low education level and knowledge of sharks resulting in more negative perceptions towards these species. Prejudice towards sharks stemmed as a potentially limiting factor because some positive effects of other variables were superseded by the effects of negative prejudice. Other practical factors such as age, economic level, and gender, also influenced respondent’s knowledge and perceptions and could provide a guidance for optimizing socioenvironmental gains relatively to public engagement efforts. Results also suggested that populations inhabiting regions with high shark bite incidence likely require distinct outreach methods because some factors underlying knowledge and perception dynamics exhibited structural differences in their effects when compared to the trends observed in a marine protected area. Altogether, public perceptions and attitudes towards sharks could be feasibly enhanced with educational development and nature experiencing strategies. Moreover, disseminating shark-specific knowledge across the society might catalyze support for the conservation of these species in a cost-effective way. This study provides a potentially useful socioenvironmental framework to deal with the human dimensions of shark management and to strengthen conservation policies aimed at promoting societal compliance with pro-environmental values, which is crucial to endow shark populations with effective protection from anthropogenic threats.